Silence of Beclin1 in oral squamous cell carcinoma cells promotes proliferation, inhibits apoptosis, and enhances chemosensitivity - Wang, Xia (Int J Clin Exp Pathol, 2017)
Increasing evidence indicates that autophagy plays an important role in regulating proliferation and apoptosis in several human diseases, including cancer. Beclin1 is the first tumor-suppressor gene in mammals involved in the regulation of autophagy. However, the function of Beclin1 in oral cancer cells is not clear at present. We investigated the effects of Beclin1 on the biological characteristics of oral carcinoma cells by Small interfering RNA (siRNA) technology. We found that Beclin1 silencing promoted proliferation, migration, and invasion of oral squamous cell carcinoma cells, and inhibited apoptosis primarily associated with upregulation of survivin and bcl-2. Further, Beclin1 silencing enhanced chemosensitivity to cisplatin. Thus, the Beclin1 gene is expected to become a new therapeutic target for oral cancer.